Proposal for a new nomenclature for CYP51 haplotypes in Zymoseptoria tritici and analysis of their distribution in Europe. (29th June 2018) - Huf, A.; Rehfus, A.; Lorenz, K. H.; Bryson, R.; Voegele, R. T.; Stammler, G.
Abstract : Zymoseptoria tritici causes septoria tritici blotch (STB), one of the most devastating diseases of wheat worldwide. C‐14 demethylation inhibitors (DMIs) belong to the most relevant fungicides in the control of STB. Intensive and long‐lasting exposure to DMIs has led to an adaptation of Z. tritici towards these fungicides. The most important mechanism leading to reduced DMI sensitivity is based on the accumulation of mutations in the CYP51 gene. Different attempts have been made to describe CYP51 haplotypes in the past. However, due to the ongoing evolution of CYP51, a new nomenclature has become necessary. This study has developed such a new nomenclature and used it to adequately describe 33 different CYP51 haplotypes found in a collection of 331 isolates across Europe in 2016. Nine of these haplotypes were found to represent 85% of all isolates, and have a heterogeneous distribution across Europe. Haplotypes carrying the substitution S524T, which is associated with a decreased sensitivity of Z. tritici to all DMIs, were only found at frequencies of around 5%. These haplotypes were mostly identified in Ireland and the UK and at lower frequencies in Germany, the Netherlands, Poland and France. In vitro studies using epoxiconazole and prothioconazole‐desthio revealed similar trends of the nine most frequent haplotypes with respect to their sensitivity towards these compounds. The data here confirm the ongoing evolution of CYP51 in the European population of Z. tritici and helps to establish a new, easy‐to‐apply nomenclature to support future descriptions of CYP51 haplotype development and evolution.